Foreign investment in the EU - Gregori, Wildmer,Nardo, Michela,Ndacyayisenga, Nathalie,Rancan, Michela (Publications Office of the European Union, 2019)
This report describes the process to construct the foreign ownership dataset called FOWN. It includes three pieces of data: i) public and private firms located in Europe controlled by non-European investors, ii) Mergers and Acquisitions (M&A) of firms located in Europe done by non-European investors, and iii) greenfield investments aiming at setting-up an installation in Europe by non-European investors. This document details the raw data used, the assumptions necessary to construct the dataset and limitations of FOWN.
10.2760/587070
Keywords: Amtsdruckschrift; Graue Literatur; Auslandsinvestition; Multinationales Unternehmen; Übernahme; Greenfield-Investition; Datenverarbeitung; Daten; EU-Staaten; foreign investment; data collection; data processing; private sector; public sector; business policy; European Union; merger; research report